Intraventricular Ciprofloxacin Usage in Treatment of Multidrug-Resistant Central Nervous System Infections: Report of Four Cases - KEPENEKLİ KADAYİFCİ, EDA (My University, 2014)
In recent years, multidrug-resistant microorganisms appear as important nosocomial pathogens which treatment is quite difficult. As sufficient drug levels could not be achieved in cerebrospinal fluid during intravenous antibiotic therapy for central nervous system infections and due to multidrug-resistance treatment alternatives are limited. In this study, four cases of central nervous system infections due to multidrug-resistant microorganisms who were successfully treated with removal of the devices and intraventricular ciprofloxacin are presented. In conclusion, intraventricular ciprofloxacin can be used for treatment of central nervous system infections if the causative microorganism is sensitive to the drug and no other alternative therapy is available.
Intraventricular Ciprofloxacin Usage in Treatment of Multidrug-Resistant Central Nervous System Infections